5. Narration - Bjork C (Pod Uni podcast, 2021)
Producer-host Dr Collin Bjork introduces you to two key aspects of podcast narration: writing for audio and vocal delivery. We open by talking about how your language as the host/narrator is linked to your relationship with your audience, topic, and interviewees. In the middle, we’ve got lots of tips and tricks. And we conclude by emphasizing the significance of using your own voice and language rather than trying to mimic someone else’s.